Evaluation of Public – Private Partnerships in Housing Provision in Minna and FCT Abuja, Nigeria - Jimoh, Richard; Emmanuel, Legbo; Paul, Bajere (Universitas Indonesia, 2015)
Against the background of the need to provide affordable housing to its people in the Federal Capital City Abuja and in Minna, the Federal Capital Development Authority and Niger state Government entered into a number of partnerships with the private sector. Most of the partnerships have reached maturity stage, but the resultant outcomes are yet to be determined. Hence, the study evaluated Public-Private Partnership (PPP) in housing provision in Minna and FCT Abuja through the self-administration of 640 structured questionnaires to the occupants of 5 housing estates in the two areas. In addition to this, five interviews were conducted for the agencies responsible for the estates. Findings from the study indicated that only 5.8% of the occupants (respondents) were the low income earners that benefited from the 5 housing estates selected and 38.4% of the respondents were satisfied with quality of work done by the developers. It was discovered that 40.9% of the respondents contributed between 31-40% of their monthly income on repayment. Bureaucratic bottleneck was one of the challenges faced in the implementation of PPP in housing provision among others. Housing provided using PPP is still skewed towards the medium and high income groups living vast majority of the low income group in limbo. Efforts should be intensified by the government in creating conducive environment for mortgage financing to thrive in order to create avenue for the low income group access to mortgage so that the huge housing deficit could be bridged.